2008
DOI: 10.1111/j.1749-7345.2008.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Dietary Mannan Oligosaccharides to Juvenile Nile Tilapia, Oreochromis niloticus, Has No Effect on Hematological Parameters and Showed Decreased Feed Consumption

Abstract: Impaired immune system by environmental stressors can lead fishes to be more susceptible to diseases that limit the economic development of aquaculture systems. This study was set out to determine the effect of six levels of mannan oligosaccharides (MOS; ActiveMOS®; Biorigin, Lençois Paulista, São Paulo , Brazil) on the performance index and hematology of Nile tilapia, Oreochromis niloticus juveniles. Fish (13.62 g) were randomly distributed into 18 plastic aquaria (300 L; 20 fishes per aquarium) and fed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 19 publications
(29 reference statements)
14
39
3
3
Order By: Relevance
“…Contrary to the present findings, there are some reports of negative effects of dietary mannan oligosaccharide on other fish species such as Gulf sturgeon (Acipenser oxyrinchus desotoi) (Pryor et al, 2003), African catfish (Clarias gariepinus) (Genc et al, 2006), Hybrid tilapia (Oreochromis niloticus×O. aureus) (Genc et al, 2007), Channel catfish, Ictalurus punctatus (Welker et al, 2007), Nile tilapia (Oreochromis niloticus) (Sado et al, 2008), sea bream (Sparus aurata) (Dimitroglou et al, 2010), Kutum (Rutilus frisii kutum) (Akrami et al, 2010) and Giant sturgeon (Huso huso) juvenile (Razeghi et al, 2012). These negative effects may be attributed to the inability of intestinal microbiota to ferment excessive levels of prebiotics and subsequent accumulation in the intestine which may be deleterious to the enterocytes (Soleimani et al, 2012).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Contrary to the present findings, there are some reports of negative effects of dietary mannan oligosaccharide on other fish species such as Gulf sturgeon (Acipenser oxyrinchus desotoi) (Pryor et al, 2003), African catfish (Clarias gariepinus) (Genc et al, 2006), Hybrid tilapia (Oreochromis niloticus×O. aureus) (Genc et al, 2007), Channel catfish, Ictalurus punctatus (Welker et al, 2007), Nile tilapia (Oreochromis niloticus) (Sado et al, 2008), sea bream (Sparus aurata) (Dimitroglou et al, 2010), Kutum (Rutilus frisii kutum) (Akrami et al, 2010) and Giant sturgeon (Huso huso) juvenile (Razeghi et al, 2012). These negative effects may be attributed to the inability of intestinal microbiota to ferment excessive levels of prebiotics and subsequent accumulation in the intestine which may be deleterious to the enterocytes (Soleimani et al, 2012).…”
Section: Discussioncontrasting
confidence: 49%
“…In 2007, Welker and his colleagues reported that 0.2% dietary mannan oligosaccharides had no effect on the WBC, RBC, Hct, Hb and total serum protein of Channel Catfish (Ictalurus punctatus) (Welker et al, 2007). Sado et al (2008) also reported that 0.2-1.0% MOS had no effect on tilapia (Oreochromis niloticus) RBC, WBC, Hb, Hct, MCV, MHC, MCHC or plasma total protein. Razeghi et al (2012) who evaluated the effects of different levels of dietary mannan oligosaccharides (2.0 and 4.0 g kgG 1 ) on the beluga (Huso huso) juvenile observed that there were no significant differences in hematological parameters between control and MOS treatment groups.…”
Section: Haematology and Biochemistrymentioning
confidence: 99%
“…Não houve influência significativa da suplementação com prebiótico, probiótico e simbiótico sobre o consumo total de ração e a taxa de sobrevivência (Tabela 2), o que corrobora os resultados obtidos por Azevedo et al (2015) em estudo sobre tilápia-do-nilo. A semelhança dos valores de consumo total de ração é uma indicação de que a suplementação com prebiótico, probiótico e simbiótico não alterou a palatabilidade da ração, diferentemente dos resultados obtidos por Sado et al (2008) em pesquisa sobre tilápia-do-nilo, em que a suplementação com mananoligossacarídeo provocou a redução do consumo de ração.…”
Section: Resultsunclassified
“…Alguns estudos relataram a falta de efeito da suplementação com prebiótico para peixes (Sado et al, 2008;Buentello et al, 2010), enquanto outros estudos relatam a melhoria do crescimento e da utilização do alimento (Staykov et al, 2007;Azevedo et al, 2015). As diferenças de resultados podem ser explicadas por diferenças estruturais dos prebióticos utilizados, nível e tempo de suplementação, condições de cultivo, além da espécie e tamanho do peixe.…”
Section: Resultsunclassified
“…Gültepe (2007) reported similar results for the Bio-M OS fed sea bream in 2‰ and 4‰ (P˃0.05). Different MOS levels (0, 2, 4, 6, 8, 10 g/kg) did not affect the hematological parameters in juvenile Nil tilapia and Huso huso (Sado, Almedia Bicudo, & Cyrino, 2008;Mansour et al, 2012). In terms of GOT (AST), all groups were found lower than control group.…”
Section: Discussionmentioning
confidence: 99%